Fear-Specific Amygdala Function in Children and Adolescents on the Fragile X Spectrum: A Dosage Response of the FMR1 Gene. (11th November 2012) - Kim, So-Yeon; Burris, Jessica; Bassal, Frederick; Koldewyn, Kami; Chattarji, Sumantra; Tassone, Flora; Hessl, David; Rivera, Susan M.
Abstract : Mutations of the fragile X mental retardation 1 ( FMR1 ) gene are the genetic cause of fragile X syndrome (FXS). The presence of significant socioemotional problems has been well documented in FXS although the brain basis of those deficits remains unspecified. Here, we investigated amygdala dysfunction and its relation to socioemotional deficits and FMR1 gene expression in children and adolescents on the FX spectrum (i.e., individuals whose trinucleotide CGG repeat expansion from 55 to over 200 places them somewhere within the fragile X diagnostic range from premutation to full mutation). Participants performed an fMRI task in which they viewed fearful, happy, and scrambled faces. Neuroimaging results demonstrated that FX participants revealed significantly attenuated amygdala activation in Fearful > Scrambled and Fearful > Happy contrasts compared with their neurotypical counterparts, while showing no differences in amygdala volume. Furthermore, we found significant relationships between FMR1 gene expression, anxiety/social dysfunction scores, and reduced amygdala activation in the FX group. In conclusion, we report novel evidence regarding a dosage response of the FMR1 gene on fear-specific functions of the amygdala, which is associated with socioemotional deficits in FXS.